Biocorrosion caused by microbial biofilms is ubiquitous around us. Issue 3 (15th December 2020) - Dou, Wenwen; Xu, Dake; Gu, Tingyue
Abstract : Biocorrosion is caused by microbial biofilms. It is ubiquitous around us. We must understand it in order to treat it. Summary: Biocorrosion first surfaced in the scientific literature when Richard H. Gaines associated corrosion with bacterial activities in 1910. It is also known as microbiologically influenced corrosion (MIC). In general, it covers two scenarios. One is that microbes cause corrosion directly, which usually means microbes secrete corrosive metabolites or microbes harvest electrons from a metal for respiration to produce energy. In the second scenario, microbes are behind the initiation or acceleration of corrosion caused by a pre‐existing corrosive agent such as water and CO2, by compromising the passive film (often a metal oxide film on a metal). MIC is caused by microbial biofilms. It is everywhere around us. This work dissects some notable examples with perspectives.